LEGAL ANALYSIS OF RESPONSIBILITY OF NATIONAL HEALTH ASSURANCE PROGRAM MANAGEMENT TOWARD DISASTER VICTIMS AT THE POST DISASTER STAGE - Anwar, Slamet Riyanto (Jurnal Hukum Jurisdictie, 2022)
Provisions regarding the implementation of post-disaster health insurance are regulated by 2 (two) areas of legislation, namely in the legislation in the field of disaster management and legislation in the field of health insurance. These two areas of legislation clearly regulate disaster management, implementation of rehabilitation, health insurance (health services), and funding of health insurance for disaster victims at the post-disaster stage. However, these two areas of regulation overlap and regulate each other, and have caused the relevant agencies (BPJS, BNPB, Pemda, Ministry of Health) to question which institution/agencies are most responsible (becoming the leading sector) in administering health insurance for disaster victims in the post-disaster stage. , and where is the source of the funding. This situation is the reason for BPJS not to provide health insurance services to disaster victims at the disaster stage. The reason is that disaster victims at the post-disaster stage are considered to have been borne or received financing from the Government and/or local governments, because it is feared that there double claims or double financing.